Molecular modification associated with the heat treatment of bovine milk. (October 2017) - Gathercole, Jessica; Reis, Mariza G.; Agnew, Michael; Reis, Marlon M.; Humphrey, Rex; Harris, Paul; Clerens, Stefan; Haigh, Brendan; Dyer, Jolon M.
Abstract: Raw bovine milk was heated using common industrial heat treatment conditions to determine how treatment conditions modify proteins and lipids. Processing temperature and time were found to affect both the degree and type of molecular modification. An early and consistent protein marker of heating was identified, namely the presence of the Maillard modification (carboxymethyl or carboxyethyl) at the Lys22 residue in the whey protein glycosylation-dependent cell adhesion molecule 1 (GLCM1). Observable chemical protein modifications generally initially increased with increasing temperature but decreased then under more extreme conditions. For lipids, the concentrations of free fatty acids, methylketones, and oxidised fatty acids were directly correlated with pasteurisation temperature. However, mirroring the trend for protein modification, phosphatidylcholine hydroperoxide levels first increased and then decreased at higher temperature. These protein and lipid modifications are potential markers of milk modification during processing and product development.